Resveratrol improves ex vivo mitochondrial function but does not affect insulin sensitivity or brown adipose tissue in first degree relatives of patients with type 2 diabetes - de Ligt, Marlies (Mol Metab, 2018)
OBJECTIVE: Resveratrol supplementation improves metabolic health in healthy obese men, but not in patients with type 2 diabetes (T2D) when given as add-on therapy. Therefore, we examined whether resveratrol can enhance metabolic health in men at risk of developing T2D. Additionally, we examined if resveratrol can stimulate brown adipose tissue (BAT). METHODS: Thirteen male first degree relatives (FDR) of patients with T2D received resveratrol (150 mg/day) and placebo for 30 days in a randomized, placebo controlled, cross-over trial. RESULTS: Resveratrol significantly improved ex vivo muscle mitochondrial function on a fatty acid-derived substrate. However, resveratrol did not improve insulin sensitivity, expressed as the rate of glucose disposal during a two-step hyperinsulinemic-euglycemic clamp. Also, intrahepatic and intramyocellular lipid content, substrate utilization, energy metabolism, and cold-stimulated (18)F-FDG glucose uptake in BAT (n = 8) remained unaffected by resveratrol. In vitro experiments in adipocytes derived from human BAT confirmed the lack of effect on BAT. CONCLUSIONS: Resveratrol stimulates muscle mitochondrial function in FDR males, which is in concordance with previous results. However, no other metabolic benefits of resveratrol were found in this group. This could be attributed to subject characteristics causing alterations in metabolism of resveratrol and thereby affecting resveratrol's effectiveness. CLINICALTRIALS.GOV ID: NCT02129595.